Palm oil as an alternative to biodiesel production: Sime Darby Biodiesel Sdn. Bhd. Carey Island, Banting, Selangor / Mohammad Shahrir Mohd Subri - Mohd Subri, Mohammad Shahrir (Faculty of Plantation and Agrotechnology, 2016)
This case study was made is to see clearly about the biodiesel processing steps and also the factor of low demand of biodiesel among Malaysian. In relation, this case study is not only focusing on biodiesel industry in Malaysia but also on global issue. Indeed, while the biodiesel existence, the issue like GST and advertising of biodiesel uses has being the problem of low demand of biodiesel use in Malaysia. However, biodiesel process is also the factor that cause low demand because the catalyst that too expensive in price and complicated structure. Result shows that global research stated the uses of biodiesel is above the usage of diesel. Moreover, biodiesel usage can give positive impact like decreasing natural resource such as diesel and petroleum, thus it also could stabilize the environment. This case study has been done in Sime Darby Biodiesel Sdn. Bhd. Carey Island Banting, Selangor.